Metallosis in Sequelae of Prosthetic Revision for Ceramic Components Fracture: A Case Report with Clinical Presentation Mimicking Periprosthetic Hip Infection - Artiaco, Stefano; Fusini, Federico; Zoccola, Kristijan; Massè, Alessandro; Colzani, Giulia (Joints, 2019)
Ceramic on ceramic total hip arthroplasties have been developed and widely used during last decades because of their long-term survival and biomechanical properties. One of the most dangerous complication of these implants is the fracture of the ceramic components. The management of this condition should be carefully planned and the choice of the new implant is crucial. We describe a rare case of severe hip synovitis due to massive metallosis in sequelae of mismanaged prosthetic revision for fracture of the ceramic acetabular liner with an unusual clinical presentation that simulate a periprosthetic infection.
Keywords: metallosis; hip synovitis; periprosthetic hip infection; fracture of ceramic acetabular liner